BRICS: the coalition evolution throughout seven years - Desiderá Neto, Walter Antonio (2015)
This article has the purpose to analyze the evolution of BRICS operating as an international coalition. It is noticed that their relations have gone through two phases, by means of experienced changes upon the international context as of 2008 to 2015. The first, from 2009 to 2012, when the foreign dimension block was privileged. The second, from 2013 to 2015, when the crisis was felt more severely by the five countries, of which a considerable round of discussion was opened to entice the internal agenda among BRICS. Therefore, the text is organized as follows: after a brief contextualizing introduction, in the second section it is analyzed the manner in which the foreign dimension of the grouping had evolved. The internal dimension of the block is scrutinized in the third section. Finally, the last section renders conclusion for the purpose to connect these two dimensions with certain important events which marked the international scenario throughout this period.